INDIE CINEMA CENTRE DENGAN PENDEKATAN ARSITEKTUR BERKELANJUTAN DI KOTA BANDUNG - Ella Afrianty; Ahmad Farkhan; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2015)
Designing of Indie Cinema Centre in Bandung based on rapid development of indie film, the efforts from government in increase creative space for community and also Bandung has potential from elected in pilot poject of Asia Creative Cities. The purpose of this designing is to design coordinating institution for indie community so they can appreciate their works to the mass. This day. indie film community still use public area which not special designed for them. The main problem of this design is how to design Indie Cinema Centre by applying Sustainable Architecture in building. Sustainable Architecture applied in building, such as façade building, material and building utility. Beside applying Sustainable Architecture, this design also uses film characteristic, such one way communication and expression freedom. The result of this design from applying Sustainable Architecture and film characteristic is to obtain building shape which is take advantage of natural resources, using exterior and interior from merger of Sustainable Architecture and film characteristic, use fine material which not give negative effect for environment and applying Sustainable Architecture for water utility, electricity power and artificial air. Keywords: Sustainable Architecture, Indie Film, Community, Film Characteristic, Bandung.